Integrative Conceptual Model of Public Services in Islands Characterized Regions Through a Study of Multidimensional Literature Synthesis - Genova Furu; Dian Ferriswara; Sarwani Sarwani (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This research aims to develop an Integrative Conceptual Model of Public Services in Archipelago Characterized Regions through a study of multidimensional literature synthesis. The focus of the research is directed at four main dimensions, namely maritime infrastructure, adaptive legal frameworks, geography-based governance, and digital innovation, which interact with each other in forming an effective, adaptive, and sustainable public service system. The method used is qualitative research based on non-SLR literature review with a narrative-integrative approach according to the guidelines of (Winarno, 2020). A total of 15 national and international articles were analyzed using thematic coding and cross-dimensional synthesis techniques to identify patterns of interconnectedness between variables. The results show that maritime infrastructure is the foundation of service accessibility, adaptive legal frameworks ensure policy legitimacy and fairness, geography-based governance strengthens the effectiveness of decentralization, and digital innovation accelerates efficiency and public participation. The synthesis of these findings gave birth to a new conceptual framework called the Integrated Maritime Public Service Framework, which emphasizes the importance of synergy between physical, social, legal, and technological aspects of the archipelago. The conclusion of the study confirms that the paradigm of public service in the archipelago has shifted from a bureaucratic model to an integrative and collaborative approach based on Pancasila values. This research contributes to the development of public governance theory and provides a new direction for service policy in the Indonesian archipelago.